Induksi Perakaran Tunas Tetrastigma rafflesiae Miq. Pada Media Murashige-Skoog Dengan Penambahan Beberapa Konsentrasi Indole-3-Butyric Acid (IBA) secara In Vitro - Febriyanti, Erni; Suwirmen, -; Idris, M. (Universitas Andalas, 2013)
An experiment on in vitro root induction of Tetrastigma rafflesiae Miq. on Murashige-Skoog (MS) medium suplemented with several concentrations of Indole-3-Butyric Acid (IBA) had been done from February to April 2013. The aims of this experiment was to determine physiological responses of T. rafflesiaeâs shoot to the IBA on half strength media of MS for root induction stages. The experiment used a completely randomized design in seven treatments and four replications. The treatment was the addition of IBA in several concentration (i.e. 0.0; 0.5; 1.0; 1.5; 2.0; 2.5 and 3.0 mg/l). The results showed 0.5 mg/l suplemented IBA was more effective and efficient in root induction of shoot then other concentrations. It influenced the average number of roots (12.5 root/plantlet), the average length of root (4.98 cm) and the morphological of plantlets. The result indicated that plantlet of T. rafflesiae generated in in vitro have a higher possibility of artificial culture and give light for future conservation of Rafflesia.Keywords : Tetrastigma rafflesiae Miq., root induction, Indole-3-Butyric-acid.